2014
DOI: 10.5116/ijme.53f5.ee77
|View full text |Cite
|
Sign up to set email alerts
|

Medical education and informal teaching by nurses and midwives

Abstract: ObjectivesThe aim of this study was to examine the contribution of nurses and midwives to the education of medical colleagues in the clinical context.MethodsThe research design was a cross-sectional survey using an online questionnaire. A subsample of 2906 respondents, from a total of 4763 nurses and midwives participating in a web-based study, had taught doctors in the 12 months prior to the survey. The questionnaire generated mainly categorical data analysed with descriptive statistics.ResultsIn the group of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Lastly, nurses in our study emphasized their role in teaching hard skills, soft skills , and field wisdom , but medical trainees did not seem to acknowledge the last two to the same degree. This is consistent with a survey of 2906 nurses who had taught medical trainees, which found that 87% of nurses felt teaching trainees was part of their job, but that their teaching contributions were not recognized by the trainees and only a few had received time allowance or financial remuneration for their teaching role [ 16 ]. Moreover, a survey of first-year medical students found that these students perceived nurses as having lower academic ability, competence, and status than doctors [ 17 ].…”
Section: Discussionsupporting
confidence: 87%
“…Lastly, nurses in our study emphasized their role in teaching hard skills, soft skills , and field wisdom , but medical trainees did not seem to acknowledge the last two to the same degree. This is consistent with a survey of 2906 nurses who had taught medical trainees, which found that 87% of nurses felt teaching trainees was part of their job, but that their teaching contributions were not recognized by the trainees and only a few had received time allowance or financial remuneration for their teaching role [ 16 ]. Moreover, a survey of first-year medical students found that these students perceived nurses as having lower academic ability, competence, and status than doctors [ 17 ].…”
Section: Discussionsupporting
confidence: 87%
“…The respect shown by the students towards the midwives in this study is especially important as in a previous publication from another centre nearly half of nurses and midwives (43.9%) reported that their contributions to medical education was unrecognized by the doctors and students that they taught [2].…”
Section: Main Findingsmentioning
confidence: 54%
“…After years of teaching by scientists and medical academics, it is often the first time that the students are taught directly by midwives, who work as independent practitioners and teach students the normal and abnormal variants of labour. Much of the research in this area focuses on midwives experiences of teaching medical students, or patient's perceptions [1][2][3][4]. A successful teaching strategy should also involve the experiences of medical students, including determining whether learning objectives were achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Educators take on the expected role of providing formal teaching to meet their requirements set by their institution. As part of the multidisciplinary team, nurses, midwives and other members of the labour ward team abundantly provide informal teaching to medical students that is often left unrecognized and underappreciated (Gilmour, 2014). These professionals are not financially compensated for their contributions or acknowledged for their role in teaching medical students, yet their work is appreciated by the students and a very necessary part of their education.…”
Section: Make the Aims Clear To All Staffmentioning
confidence: 99%
“…Formal training for midwives with regards to preceptorship and adult education could be implemented to remedy this issue, as well as incentivizing midwives who have an interest in teaching through provision of a wider array of opportunities within this realm (Gilmour, 2014).…”
Section: Make the Aims Clear To All Staffmentioning
confidence: 99%